Transpalatal Approaches to the Skull Base and Reconstruction: Indications, Technique, and Associated Morbidity - London, Nyall R. (Semin Plast Surg, 2020)
Multiple anterior surgical approaches are available to obtain access to the nasopharynx, clivus, and craniocervical junction. These include the direct and transoral robotic surgery transpalatal, maxillary swing, and endoscopic endonasal approaches. In this article, we describe the indications for these techniques, surgical steps, and associated morbidities. This article is a PubMed literature review. A review of the literature was conducted to assess the techniques, surgical steps, and associated morbidities with transpalatal approaches to the skull base and nasopharynx. The transpalatal approach has been traditionally utilized to obtain surgical access to the nasopharynx, clivus, and craniocervical junction. Morbidity includes velopalatine insufficiency due to shortening of the soft palate from scar contraction or neuromuscular damage, thus leading to hypernasal speech and dysphagia. Middle ear effusion and oronasal or oronasopharyngeal palatal fistula are additional potential morbidities. The choice of surgical approach depends on a variety of factors including the disease location and extent, surgeon experience, and available resources.